Conceptualizing and operationalizing human wellbeing for ecosystem assessment and management. Issue 66 (December 2016) - Breslow, Sara Jo; Sojka, Brit; Barnea, Raz; Basurto, Xavier; Carothers, Courtney; Charnley, Susan; Coulthard, Sarah; Dolšak, Nives; Donatuto, Jamie; García-Quijano, Carlos; Hicks, Christina C.; Levine, Arielle; et al.
Graphical abstract: Highlights: We present a detailed framework of human wellbeing for ecosystem-based management. Connections, capabilities, and conditions may be assessed using indicators. Cross-cutting analyses can assess equity, security, resilience, and sustainability. The framework and focal attributes should be modified to serve diverse contexts. 2300 existing social indicators are compiled from which to select measures. Abstract: There is growing interest in assessing the effects of changing environmental conditions and management actions on human wellbeing. A challenge is to translate social science expertise regarding these relationships into terms usable by environmental scientists, policymakers, and managers. Here, we present a comprehensive, structured, and transparent conceptual framework of human wellbeing designed to guide the development of indicators and a complementary social science research agenda for ecosystem-based management. Our framework grew out of an effort to develop social indicators for an integrated ecosystem assessment (IEA) of the California Current large marine ecosystem. Drawing from scholarship in international development, anthropology, geography, and political science, we define human wellbeing as a state of being with others and the environment, which arises when human needs are met, when individuals and communities can act meaningfully to pursue their goals, and when individuals and communities enjoy a satisfactory quality of life . We propose four major social science-based constituents of wellbeing: connections, capabilities, conditions, and cross-cutting domains. The latter includes the domains of equity and justice, security, resilience, and sustainability, which may be assessed through cross-cutting analyses of other constituents. We outline a process for identifying policy-relevant attributes of wellbeing that can guide ecosystem assessments. To operationalize the framework, we provide a detailed table of attributes and a large database of available indicators, which may be used to develop measures suited to a variety of management needs and social goals. Finally, we discuss four guidelines for operationalizing human wellbeing measures in ecosystem assessments, including considerations for context, feasibility, indicators and research, and social difference. Developed for the U.S. west coast, the framework may be adapted for other regions, management needs, and scales with appropriate modifications.